A educação em direitos humanos e a formação de professores da educação básica na arquitetura normativa internacional e nacional: contribuições para a construção das culturas de direitos humanos e de direitos fundamentais - Gonzalez, Cristiani Pereira de Morais (2021)
The present thesis aims to study the education in human rights and the formation of basic education teachers for its teaching acording to the norms of the United Nations and the Brazilian State, which has been adopted since the end of the Second World War. The choice for this object of research took into account the social relevance of the theme and the originality of the study. It also considered the relevance of the “Social Inclusion, Protection and Defense of Human Rights” research line. The guiding question of the research consists of how education in human rights and the training of basic education teachers on such rights are outlined in the normative documents of the United Nations and the Brazilian Constitutional State, and how they contribute (or not) to the building of the cultures of human rights and fundamental rights. Based on the hypothesis that human rights education and the training of basic education teachers for its teaching are outlined out of universalist conceptions of human rights, pointing to the development of a culture of such rights, one defined as the general objective of the research to analyze how human rights education and the training of basic education teachers in such rights are outlined in the normative instruments referred to, and how they contribute (or not) to building cultures of human rights and fundamental rights. This thesis specifically aims to define human rights, fundamental rights, Constitution, citizenship, education and teacher training in a cultural context of valuing the rights of the human species, to identify and detail the instruments belonging to the global and national systems for the protection of human rights, which allude to education in such rights and/or the training of teachers for its teaching, to specify and examine the normative instruments of the UN and the Brazilian State, which outline human rights education and the training of basic education teachers, viewing to build cultures of human rights and fundamental rights. The methodological aspects are carried out through a documental research and a content analysis of the corpus, which is composed of ten documents, five of which belonging to the UN framework, and five other more belonging to the national legal order. The analysis showed that the analyzed documents provide a contribution to the construction of cultures of human rights and fundamental rights in general, because they establish and often reiterate, among other things, concepts, principles, objectives, and measures to be adopted, all of which aimed at a socialization in a culture of respect, defense and promotion of human rights. It is necessary though to emphasize that the documents that have become the object of analysis contribute in different ways and in different degrees to the construction of such cultures, containing points that deserve to be improved. The UN program, for instance, needs to go deeper into the subjects of “education” and “teacher training”, while within the Brazilian legal order, human rights need to be expressely anticipated in all documents that deal with education and training of basic education teachers in such rights.